Building a Sensor Benchmark for E-Nose Based Lung Cancer Detection: Methodological Considerations - Justin D. M. Martin; Anne-Claude Romain (Chemosensors, 2022)
Lung cancer is one of the deadliest form of cancer in Europe, characterized by a lack of obvious symptoms until the terminal stages of the illness. Electronic noses are a rising screening technology to detect early-stage lung cancer directly in the homes of people at risk. Electronic noses need to be tested using samples from patients. However, obtaining numerous samples from cancer patient turns out to be a difficult task in practice. Therefore, the development of a sensor benchmark able to evaluate the performance of sensors without direct breath sampling is of high interest. This paper focuses on the methodology for developing such a benchmark, in the case of a breath sampling electronic nose. The setup used is introduced and general recommendations based on literature and undergoing experiments is detailed. The benchmark can be used for a variety of sensors and a variety of target illnesses. It is also possible to apply it to other types of medical gaseous samples or environmental VOC monitoring. The benchmark is currently still undergoing tests, and results will be published in a following article.